Gambaran Deskriptif Perilaku Penggunaan Alat Pelindung Diri dan Angka Kejadian Tertusuk Jarum Suntik pada Tenaga Kesehatan Gigi di Puskesmas Kabupaten Wonogiri - Prasetyo, Andhika Galih; , drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K); , drg. Fitria Nur Malita Sari (2015)
Personal protective equipment is the one of the elements in the universal precautions to minimize the risk of cross-infection that may be experienced by dental health workers when dealing with patients in all health care facilities. Personal protective equipment included mask, gloves, goggles and protective clothing. The purpose of this study is to describe the behavior of the use of personal protective equipment and describe the incidence of needlestick injuries in dental health workers in health centers in Wonogiri, Central Java. This research is a descriptive observational study (survey) with cross- sectional design survey. The study population is the entire dental health workers in health centers Wonogiri totaling 46 people. Data collected using direct observation, interviews and questionnaires about the incidence of needlestick injuries. The results showed that the use of gloves on dentist is about 95.45% and 95.83% on dental nurse. The use of masks on dentist and dental nurse is about 100%. Meanwhile, the use of protective goggles and protective clothing shows the results of 0%. The results of the study shows that incidence of needlestick injuries is about 28.26%. The conclusion of the research showed that dental health workers behavior towards the use of personal protective equipment such as gloves and masks have described a good behavior, while the behavior of the use of protective goggles and protective clothing is still not good. In addition, it can be concluded that the proportion of needlestick incident on dental health workers in health centers in Wonogiri is about 28.26%. This suggests that dental health workers in health centers Wonogiri have a pretty good precaution in preventing the risk of cross-infection.